Equação de Schrödinger não linear com coeficientes modulados - Arroyo Meza, Luis Enrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this thesis we deal with the nonlinear Schrödinger equation with modulated coefficients in different contexts. This nonlinear differential equation is widely used to describe light pulses propagating through an optical fiber or to model the dynamics of a Bose-Einstein condensate. First, we apply point canonical transformations to solve some classes of nonlinear Schrödinger equation with modulated coefficients namely, those which possess specific cubic and quantic (time- and space-dependent) nonlinearities. The method applied here allows us to find wide localized (in space) soliton solutions to the nonlinear Schrödinger equation, which were not presented before. In the context of Bose-Einstein condensates, we also generalize the external potential which traps the system and the nonlinearities terms. Then, we apply point canonical transformations to solve some classes of two coupled nonlinear Schrödinger equations with modulated coefficients namely, specific cubic and quantic - time and space dependent - nonlinearities. The method applied here allows us to find a class of wide localized (in space) vector soliton solutions of two coupled nonlinear Schrödinger equations. The vector solitons found here can be applied to theoretical studies of Bose-condensed atoms in two different internal states and of ultrashort pulse propagation in optical fibers with focusing and defocusing nonlinearities. Finally, we use point canonical transformations to obtain localized (in space) exact solutions of the nonlinear Schrödinger equation with cubic and quantic space and time modulated nonlinearities and in the presence of time-dependent and inhomogeneous external potentials and amplification or absorption (source or drain) term. We obtain a class of wide localized exact solutions of nonlinear Schrödinger equation in the presence of a number of non-Hermitian ... (Complete abstract click electronic access below)

Nesta tese lidamos com a equação de Schroedinger não linear com coeficientes modulados em diferentes contextos. Esta equação diferencial não linear é amplamente usada para descrever a propagação de pulsos de luz através de uma fibra óptica ou para modelar a dinâmica de um condensado de Bose-Einstein. Primeiro, aplicamos as transformações canônicas de ponto para resolver algumas classes de equação de Schroedinger não linear com coeficientes modulados ou seja, aqueles que possuem não linearidades cúbica e quântica (dependentes do espaço e tempo) específicas. O método aplicado aqui nos permite encontrar soluções tipo sólitons localizados (no espaço) para a equação de Schroedinger não linear com coeficientes modulados, que não foram apresentados antes. No contexto de condensados de Bose-Einstein, nós generalizamos o potencial externo o qual armadilha o sistema, e os termos de não linearidade da equação diferencial. Em seguida, aplicamos as transformações canônicas de ponto para resolver algumas classes de duas equações de Schroedinger não lineares acopladas com coeficientes modula-dos isto é, não linearidades cúbica e quântica - dependentes do espaço e tempo - específicas. O método aplicado aqui nos permite encontrar uma classe de soluções de sólitons tipo vetoriais localizados (no espaço) das duas equações de Schroedinger não linear acopladas. Os sólitons vetoriais encontrados aqui podem ser aplicados a estudos teóricos de condensados de Bose-Einstein de átomos com dois estados internos diferentes ou á propagação de pulsos de luz através de fibras ópticas focalizadoras ou desfocalizadoras. Finalmente, usando transformações canônicas de ponto obtemos soluções exatas localizadas (no espaço) da equação de Schroedinger não linear com não linearidades cúbica e quântica moduladas no espaço e tempo ...(Resumo completo, clicar acesso eletrônico abaixo)
Nonlinear Schrödinger equation with modulated coefficients
Keywords: Solitons; Ondas não-lineares; Schrodinger, Equação de; Fibras oticas; Condensação de Bose-Einstein; Schrodinger equation